2019
DOI: 10.1155/2019/5081909
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Histogram Analysis Parameters Derived from DCE-MRI and Histopathological Features including Expression of EGFR, p16, VEGF, Hif1-alpha, and p53 in HNSCC

Abstract: Background Our purpose was to elucidate possible correlations between histogram parameters derived from dynamic contrast-enhanced MRI (DCE-MRI) with several histopathological features in head and neck squamous cell carcinomas (HNSCC). Methods Thirty patients with primary HNSCC were prospectively acquired. Histogram analysis was derived from the DCE-MRI parameters: Ktrans, Kep, and Ve. Additionally, in all cases, expression of human papilloma virus (p16) hypoxia-inducible factor-1-alpha (Hif1-alpha), vascular e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 40 publications
(63 reference statements)
0
16
0
Order By: Relevance
“…Recent studies reported that diffusion-weighted imaging (DWI) may help predict HPV status in patients with OPSCC, as HPV-positive OPSCC reveals a low mean apparent diffusion coefficient (ADC) compared with HPV-negative OPSCC 9 11 . Furthermore, a histogram analysis based on dynamic contrast-enhanced MR image showed significantly higher K ep kurtosis values and lower V e min values in patients with p16-positive OPSCC 12 . Recently, several published studies had addressed the prediction of HPV status employing a CT-based radiomics approach; however, their diagnostic performance was moderate (area under the curve; AUC, 0.75–0.80) 13 15 .…”
Section: Introductionmentioning
confidence: 89%
“…Recent studies reported that diffusion-weighted imaging (DWI) may help predict HPV status in patients with OPSCC, as HPV-positive OPSCC reveals a low mean apparent diffusion coefficient (ADC) compared with HPV-negative OPSCC 9 11 . Furthermore, a histogram analysis based on dynamic contrast-enhanced MR image showed significantly higher K ep kurtosis values and lower V e min values in patients with p16-positive OPSCC 12 . Recently, several published studies had addressed the prediction of HPV status employing a CT-based radiomics approach; however, their diagnostic performance was moderate (area under the curve; AUC, 0.75–0.80) 13 15 .…”
Section: Introductionmentioning
confidence: 89%
“…Considering the volume of data that can be derived from both histology and functional imaging, radiologists and clinicians should be aware of the different potential roles of several biomarkers with respect to specific clinical end points. To this purpose, a number of reports have recently evaluated the complementarity and/or associations between imaging and histopathological features in HNSCC [10][11][12][13][14][15], as well as in different malignancies, i.e. breast cancer, lung adenocarcinoma and glioma [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The disadvantage of these methods is that they need invasive methods to obtain tissue samples, local samples often can't re ect the whole tumor situation, and samples in vitro can't really re ect the metabolism situation in vivo. DCE-MRI quantitative perfusion histogram can detect the metabolic activity inside the tumor from the molecular level based on the gray-scale intensity information of the lesion site and describe the heterogeneity of the lesion [8][9][10]. Therefore, the purpose of this study is to investigate the correlation between the DCE-MRI histogram parameters and PTEN, P-Akt, and m-TOR of lung cancer, so as to provide a basis for non-invasive prediction of P13K / Akt / mTOR signal pathway gene activation in lung cancer tissue by DCE-MRI histogram parameters.…”
Section: Introductionmentioning
confidence: 99%